Sistem Informasi Manajemen Rumah Sakit (SIMRS) Untuk Meningkatkan Mutu Pelayanan Kesehatan Di Indonesia - Maya Saufinah Pane; Nirmaya Fanisya; Silvi Roma Rizkina; Yesy Prinkawati Nasution; Dewi Agustina (Pusat Riset dan Inovasi Nasional, 2023)
The quality of service at hospitals must always be improved to provide the best service to people in Indonesia. In accordance with Permenkes Number 82 of 2013 it states that every hospital is required to implement and develop a Hospital Management Information System (SIMRS). The Hospital Management Information System (SIMRS) is very important to do to support the efficiency of the management process in hospitals starting from information to patients, data, data processing and all activities in the hospital. By implementing a Hospital Management Information System, it is necessary to know how it is applied in improving the quality of health services in Indonesia. This research was conducted with literature reviews and journal searches using Google Scholar. The research results show that the implementation of the Hospital Management Information System (SIMRS) can improve the quality of health services because it facilitates the management activities of health service institutions.